Abnormal Pyramidal Decussation and Bilateral Projection of the Corticospinal Tract Axons in Mice Lacking the Heparan Sulfate Endosulfatases, Sulf1 and Sulf2 - Aizawa, Satoshi; Okada, Takuya; Keino-Masu, Kazuko; Doan, Tri Huu; Koganezawa, Tadachika; Akiyama, Masahiro; Tamaoka, Akira; Masu, Masayuki (Frontiers in Molecular Neuroscience, 2020)
The corticospinal tract (CST) plays an important role in controlling voluntary movement. Because the CST has a long trajectory throughout the brain toward the spinal cord, many axon guidance molecules are required to navigate the axons correctly during development. Previously, we found that double-knockout (DKO) mouse embryos lacking the heparan sulfate endosulfatases, Sulf1 and Sulf2, showed axon guidance defects of the CST owing to the abnormal accumulation of Slit2 protein on the brain surface. However, postnatal development of the CST, especially the pyramidal decussation and spinal cord projection, could not be assessed because DKO mice on a C57BL/6 background died soon after birth. We recently found that Sulf1/2 DKO mice on a mixed C57BL/6 and CD-1/ICR background can survive into adulthood and therefore investigated the anatomy and function of the CST in the adult DKO mice. In Sulf1/2 DKO mice, abnormal dorsal deviation of the CST fibers on the midbrain surface persisted after maturation of the CST. At the pyramidal decussation, some CST fibers located near the midline crossed the midline, whereas others located more laterally extended ipsilaterally. In the spinal cord, the crossed CST fibers descended in the dorsal funiculus on the contralateral side and entered the contralateral gray matter normally, whereas the uncrossed fibers descended in the lateral funiculus on the ipsilateral side and entered the ipsilateral gray matter. As a result, the CST fibers that originated from 1 side of the brain projected bilaterally in the DKO spinal cord. Consistently, microstimulation of 1 side of the motor cortex evoked electromyogram responses only in the contralateral forelimb muscles of the wild-type mice, whereas the same stimulation evoked bilateral responses in the DKO mice. The functional consequences of the CST defects in the Sulf1/2 DKO mice were examined using the grid-walking, staircase, and single pellet-reaching tests, which have been used to evaluate motor function in mice. Compared with the wild-type mice, the Sulf1/2 DKO mice showed impaired performance in these tests, indicating deficits in motor function. These findings suggest that disruption of Sulf1/2 genes leads to both anatomical and functional defects of the CST.